Eukaryo: An AR and VR Application for Cell Biology - Yuen, Douglas; Santoso, Markus; Cartwright, Stephen; Jacob, Christian (International Journal of Virtual Reality, 2016)
Eukaryo is a simulated bio-molecular world that allows users to explore the complex environment within a biological cell. Eukaryo was developed using Unity, leveraging the capabilities and high performance of a commercial game engine. Through the use of MiddleVR, our tool can support a wide variety of interaction platforms including 3D virtual reality (VR) environments, such as head-mounted displays, augmented reality (AR) headsets, and large scale immersive visualization facilities. Our interactive, 3-dimensional model demonstrates key functional elements of a generic eukaryotic cell. Users are able to use multiple modes to explore the cell, its structural elements, its organelles, and some key metabolic processes. In contrast to textbook diagrams and even videos, Eukaryo immerses users directly in the biological environment, giving a more effective demonstration of how cellular processes work, how compartmentalization affects cellular functions, and how the machineries of life operate.